Periodontal disease and serum uric acid levels in the absence of metabolic syndrome: is there a link? A study on a sample of Cameroonian adults - Jan René Nkeck; Jules Julien Ndjoh; Gwladys Flora Meyo Mvondo; Manuela Eko Ondoa; Ornela Takam; Stéphane Fargeon Massin Mbouna; Daryl Tcheutchoua Nzokou; Larissa Ange Tchuisseu-Kwangoua; Claude Bernard Yvan Momo; Jean Xavier Ekouelkoum Ngoude; Marie Ida Chemgne; Vicky Jocelyne Ama Moor (BMC Oral Health)
Abstract Background The relationship between serum uric acid level (SUA) and periodontal diseases (PD) is still controversial, and few studies have been carried out in population with no element of metabolic syndrome especially in sub-Saharan Africa. The aim of this study was to assess the relationship between PD and SUA in Cameroonian adults not suffering from metabolic syndrome. Methods We carried out a cross-sectional study including Cameroonians aged over 18 years recruited in the general population and free of metabolic syndrome elements. They were assessed for frequency of consumption of purine-rich foods, periodontal indices (plaque index, gingival index, calculus index, pocket depth and clinical loss of attachment), and SUA. The diagnosis of PD was based on the American Academy of Periodontology criteria revised in 2015, and hyperuricemia was defined for values exceeding 70 and 60mg/L in men and women respectively. Comparison of SUA means was performed with the ANOVA test. Association between hyperuricemia and PD were evaluated using Fischer's exact test. The threshold of significance was 0.05. Results One hundred and seventy-four participants were included (57.5% women, mean age 29 (10.39) years). The frequencies of PD were 75.9%, gingivitis (59.1%) and periodontitis (40.1%). Hyperuricemia was found in 20.45% of people with PD, with no difference in frequency comparing with those without PD. The frequency of consumption of purine-rich foods was similar in individuals with and without PD. Serum uric acid levels were not different in individuals with and without PD, and differed among periodontal indices only for calculus index, where SUA were higher in participants with the highest score (p=0.026). We found no association between hyperuricemia and PD. Conclusion In individuals without elements of metabolic syndrome, hyperuricemia affects one in five people with PD. There appears to be no link between SUA and overall periodontal status in this population. Further studies are needed to better understand the salivary interaction between uric acid and periodontium in our population.